EGF-TM7 receptors - Hamann, Jörg; Lin, Hsi-Hsien (Henry Stewart Talks, 2012)
F4/80 is a marker for mouse macrophages, The EGF-TM7 receptors EMR1 (F4/80), EMR2, EMR3, EMR4 and CD97 belong to the adhesion class of GPCRs, Evolution, expression and structure of EGF-TM7 receptors, EGF-TM7 receptors bind cell- and matrix-associated ligands, Role of EGF-TM7 receptors in immunity